The Influence of Quality of Human Resources, Availability of Business Capital and Technological Progress on Home Industries - Siswanto, Adil (Ilomata International Journal of Social Science, 2024)
The main objectives of this research are: 1) to analyze wether quality of human resources partially influence on home industry; 2) to analyze wether Availability of Business capital partially influence on home industry; 3) to analyze wether Technological progress influence on home industry; 4) to analyze wether Quality of Human Resources, Availability of Business capital and Technological progress simultaneously influence on Home Industries. Quantitative approach with Data and instruments are primary through questionnaires. The total population is 100 people of all home industries owners in Klenang Lor Village. The total of respondents is 80 people based on the representative sampling technique and calculated by Slovin’s Formula. Based on the results, Quality of Human Resources does not influence partially with score .596 less than 1.984. The Availability of Business capital has an influence partially on home industry which t table of 1.984 (7.359 > 1.984). Technological progress has no influence partially with score .407 less than I.984 (.407 < 1.984). The Quality of Human Resources, Availability of Business capital and technological progress simultaneously influence on home industry to increase local family economic development in Indonesia with F value is 2.654 greater than 2.70 (2.654 > 2.70). Implication of this research found that partially the influence of quality of human resources, Availability of Business capital, and technological progress do not have influence on home industries, but simultaneously have influence on home industries. Technological progress does not have influence on home industries because the people make the products using manual technology.